A Network Analysis Perspective on the Relationship Between Boredom, Attention Control, and Problematic Short Video Use Among a Sample of Chinese Young Adults. - Zhou, Lian; Lv, Xin; Zhou, Yuhong; Li, Jiayu; Yu, Zhixiang; Gao, Xuemei (International Journal of Mental Health & Addiction, 2025)
Playing short videos has been an everyday leisure activity in recent years, and problematic use has raised concerns. The present study was based on the boredom feedback model, using network analysis to explain the interactive relationships between boredom, attention control, and problematic short video use (PSVU) (in domain-level analysis) and elaborate visually on the symptom presentation and associations between these variables (in facet-level analysis). A sample comprising 632 Chinese young adults (330 males) aged 18–30 years completed self-report questionnaires to assess state boredom, boredom proneness, attention control, and PSVU. The results showed significant associations between state boredom, boredom proneness, attention control, and PSVU. In domain-level network, boredom proneness was the most central node. In facet-level network, inattention had the highest strength and closeness centrality, and conflict had the highest betweenness centrality. The findings suggested the intervention of inattention and conflict in PSVU users that will contribute to future research and practice.